(untitled) (The International Research Journal of Management Science, 2017)
Internship is a profession-oriented learning technique translating the knowledge into professional skills. It helps to equip future human resources with operational skills and enhanced social relationship. Satisfaction through internship program develops different attitudes which may lead loyalty, job commitment, extended efforts, etc. As it provides more independence and opportunity of social networking, it may change the attitude of the person. This piece of research is intended to estimate the level of satisfaction among the hotel management students and explore their attitude towards their decision regarding future profession. Structured questionnaire prepared both in English and Nepali was used to collect the response. Convenient as well as snow ball sampling are used as sampling techniques. Descriptive analytical tools are used to draw the conclusion. This study concludes that majority of the students are satisfied from the intern opportunity and hence they wish to join hotel industry. This study has observed low but positive and significant relationship with satisfaction and intention of changing attitude. This study has also explored the fact that there no gender influence in satisfaction level of the intern students but male students are more prone to change on behavioural intention. Students are positive regarding their career choice but are found of developing negative attitude towards college management as well as in-college activities.